Die nuwe grondwet van Suid-Afrika - W.P. Esterhuyse (AOSIS, 1984)
The new constitution of the RSA is an attempt to break away from the Westminster system of government. A few important basic principles include a distinct separation between executive and legislative power, group representation, participation in common affairs, and the principle of consensus. The constitution provides a number of important mechanisms to enable the formulation of policy. These mechanisms include the position of the President, the President's Council and the permanent collective committees. One of the implications of the new constitution is that government departments for own affairs for a particular population group can only be headed by a Minister of the same population group. Other implications are decentralisation of power to regional levels, that we are entering an era of collective bargaining in politics and that structures for co-operation and mutual discussion will have to be be created. A constitution can be likened to the rules of a game. How the game is played, however, depends on the attitude of the players.